The Effect of Entrepreneurial Orientation on Firm Performance: The Role of Networking Capability - Arifah Rahman, Amalia; Heri Pratikto; Ely Siswanto (Brilliant International Journal Of Management And Tourism, 2022)
This study aims to determine the effect of entrepreneurial orientation on company performance. This research was also conducted to determine the role of network capabilities as mediators in the relationship between entrepreneurial orientation and company performance. This research is quantitative research with an explanatory research approach which was conducted on women entrepreneurs at the Entrepreneurs Association of Batu City. The sampling method used in this study is a saturated sample of 88 female entrepreneurs. The research data is primary data obtained through the distribution of online and offline questionnaires. The data analysis used is SEM-PLS assisted by SmartPLS 3.3.3 software. The results of this study indicate that entrepreneurial orientation has no significant effect on company performance. Entrepreneurial orientation has a positive and significant effect on network capabilities and marketing capabilities. Network capabilities and marketing capabilities have a positive and significant impact on company performance. This study also found that networking skills and marketing skills act as perfect mediators in the relationship between entrepreneurial orientation and company performance. In future research, it is necessary to consider adding samples and independent variables outside of the study